Preliminary study on the application of multiphase DEM for the prediction of fat,oil and grease (FOG) deposition in sewer pipe lines - Husain, Iman A. F.; Al-Khatib, Ma'an Fahmi Rashid; Jami, Mohammed Saedi; Mirghani, Mohamed Elwathig Saeed; Zainudin, Zaki; Hoda, Asif (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Fat oil and grease (FOG) deposition into sewer pipes can block the pipes and restrict the wastewater flow causing backflows and sanitary sewer overflows (SSOs). Understanding the wastewater flow and transport of FOG particles is a key step for predicting the particles deposition and blockage formation. In this research, ANSYS FLUENT was used for simulating the flow of FOG particles and its deposition onto the sewer pipe. The multiphase Eularian-Lagrangian model with discrete Phase method (DPM) was used for developing the CFD model. The kinetic parameters and physical values are based on previous experimental work and literature. The model will assist in predicting blockages by acting as an early warning system for the wastewater municipalities.